EFEKTIFITAS PENYELENGGARAAN KELAS AKSELERASI SMP NEGERI 1 MUNTILAN KABUPATEN MAGELANG (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This research is aimed to know the mechanism for administering the accelerated class program in State Junior High School 1 Muntilan and the effectiveness of  implementation of accelerated class program in Junior High School 1 Muntilan Magelang  Regency measured using resource approach, process approach and goals approach.The approach used in this research was qualitative descriptive approach. The research was conducted in State Junior High School 1 Muntilan Magelang Regency in 2013/2014 Academic Year which involved the headmaster, the manager of acceleration class program, the school committee, the teachers, and the students of accelerated class program as the participants of this research. The data were collected by using observation, interview, and documentation techniques. The validity and the reliability of the instrument were conducted by using triangulation technique. The data analysis used was  interactive modal which included collecting data, reducing data, presenting data and making a conclusion.The results of this study indicate that in general the implementation of an accelerated program at SMP Negeri 1 Muntilan  Magelang Regency  had been running effectively, in terms of input, process, and out put components. The effectiveness of the program in terms of acceleration input components that included the acceleration students, acceleration teachers, the curriculum and the infrastructure of acceleration program was quite effective. The evidences show that the school successfully prepared all input components as needed. The effectiveness of the program in terms of the acceleration process which included the components of teaching and learning, guidance and counseling and evaluation of learning outcomes had been effective. The effectiveness of the program in terms of the acceleration component output which included the completion of the period of study and academic achievement had also been effective. It was proved that all students were able to complete the accelerated program during the study period of 2 years with again value of the subjects tested nationally over7.5.